Overseeding Cool-Season Lawns - Leuthold, Larry D.; Fry, Jack D.; Hughes, Angela (My University, 1995)
This publication provides information on the general care and management of cool-season lawns.
MF2116_1995_05
Keywords: MF2116; Lawn and Garden; MF